TRADITIONAL MEDICINE AND MEDITERRANEAN VEGETATION IN PORTUGUESE COMMUNITY, EUROPE (FLOVET - Boletim do Grupo de Pesquisa da Flora, Vegetação e Etnobotânica, 2018)
Ethnomedicine is a way of recording traditional customs concerning the use of plants by communities. The present study constitutes a contribution to the ethnobotanical study of the medicinal and aromatic plants used in the Idanhaa-Nova Village in Portugal. The corpus of the work is composed of 40 individuals between the ages of 45 and 100. In the methodology was applied semistructured interviews, direct observation, oral history, guided tour and photographic record. Some 60 plants were identified, with emphasis on poejo, neveda, and lemon balm, wild Malvae, seven-sangria grass, corn beards and wild life. The plants are mostly used in the form of tea, for treatments of constipation, menstrual pains, urinary infections and wound infection. The Mediterranean culture is expressive as it brings traditional knowledge closer to the local ethnomedicine.Keywords: Mediterranean culture, ethnobotany, traditional community